Professional perceptions of the effectiveness of visual communication systems and their applications for functional communication interventions for individuals with Autism Spectrum Disorder. (January 2018) - Alexander, Elizabeth; Dille, Lisa
Background & aims: This study investigated the perceptions of educational professionals in regard to the effectiveness of visual communication systems and their applications as a functional communication intervention for individuals with Autism Spectrum Disorder (ASD). Methods: One hundred and one individuals from diverse educational backgrounds, school districts, educational services, and various states were surveyed for this study. All participants in this study served individuals with Autism Spectrum Disorder in a clinical and/or school setting. Results: The study found that aided augmentative and alternative communication (AAC) systems were widely utilized, and participants perceived these systems as the most effective for individuals with Autism Spectrum Disorder. It also found that the use of low level tech aided augmentative communication systems such as Picture Exchange System and high level tech systems such as voice output systems that were strictly computer based, were dependent on the individual's abilities and needs. Finally, the study found that the use of photography and photo journaling techniques had positive outcomes for individuals diagnosed with Autism Spectrum Disorder and other students in the learning environment. Conclusions: The results revealed that the overall consensus of educational professionals that serve individuals with ASD agreed that aided AAC systems were more effective methods to foster and enhance functional communication. In terms of effectiveness of the level of technology utilized within the system, it depends on the needs and abilities of the individual with ASD. Participants, however, did agree that photography and photo journaling techniques may provide positive attributes to all students and not only those diagnosed with ASD. Implications: The ability to modify or alter the ways in which AAC systems are created and implemented may address the need to individualize the systems in terms of the needs and abilities of the individual with ASD. The results inform educational practices as they highlight that a majority of the professionals that participated in this study need further professional development with the understanding and application of these systems in order to better understand their benefits and what they have to offer individuals with ASD. The results also provided a lens through the professionals' experiences into the classrooms by providing information from professionals that utilize and implement these systems daily including their successes in aiding communication effectively.